Juvenile rheumatoid arthritis associated with uveitis in a 4-year-old girl - Made Sukmawati; Hendra Santoso; Niti Susila (Indonesian Pediatric Society, 2006)
The variability of the disease may explain mis-conceptions that JRA is usually a benign disease. Acohort study in which 506 subjects during the periodof 1970-1999 found that approximately one-third ofJRA patients achieve disease remission. The visualcomplications are also important in determining theoutcome. Functional disability is common and can belong-lasting. Recognizing JRA symptoms earlier areimportant to prevent mortality, disability, and long-term complications. Although JRA is the most com-mon rheumatic disease in children, many doctors arenot familiar with this disease. The purpose of thispaper is to report a case of juvenile rheumatoid ar-thritis associated with uveitis in a 4-year, 8-month-old girl.